2005
DOI: 10.1128/jcm.43.11.5593-5600.2005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing for Differentiation of Strains of Candida tropicalis

Abstract: A system is described for typing isolates of the pathogenic fungus Candida tropicalis, based on sequence polymorphisms in fragments of six genes: ICL1, MDR1, SAPT2, SAPT4, XYR1, and ZWF1a. The system differentiated 87 diploid sequence types (DSTs) among a total of 106 isolates tested or 80 DSTs among 88 isolates from unique sources. Replicate isolates from the same source clustered together with high statistical similarity, with the exception of one isolate. However, a clade of very closely related isolates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 23 publications
1
152
2
Order By: Relevance
“…Whether any of these isolates belong to the R 5FC clone would be of interest. Of note, a recent study of 104 C. tropicalis clinical isolates recovered from various countries (9) showed that none of the 5 R 5FC isolates collected in the United Kingdom has the MLST profi le of the R 5FC clone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether any of these isolates belong to the R 5FC clone would be of interest. Of note, a recent study of 104 C. tropicalis clinical isolates recovered from various countries (9) showed that none of the 5 R 5FC isolates collected in the United Kingdom has the MLST profi le of the R 5FC clone.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the 6 MLST loci recently described were analyzed as reported in Tavanti et al (9). These loci were selected because, according to these authors, they were associated with more polymorphism (XYR1 and SAPT4) and with antifungal resistance (MDR1).…”
Section: Multilocus Sequence Typing Analysismentioning
confidence: 99%
“…There are reports about its application for several Candida species (86,116). Recently, two new techniques arouse: amplified fragment length polymorphism (AFLP) (3) and multilocus sequence typing (MLST) (12,32,115).…”
Section: Molecular Biologymentioning
confidence: 99%
“…glabrata (Dodgson et al, 2003), C. tropicalis (Tavanti et al, 2005), C. krusei , Cryptococcus neoformans var.…”
Section: Multi-locus Sequence Typing (Mlst) 분석mentioning
confidence: 99%